Effect of cold press and Soxhlet extraction systems on total carotenoid, antioxidant activity values and phytochemicals in caper (Capparis ovata var herbacea) seed oils. Issue 6 (23rd April 2021) - Al Juhaimi, Fahad; Ghafoor, Kashif; Musa Özcan, Mehmet; Uslu, Nurhan; Babiker, Elfadil E.; Mohamed Ahmed, Isam A.; Alsawmahi, Omer N.
Abstract: Total carotenoid and chlorophyll amounts of caper seed oils extracted in cold press and Soxhlet extraction methods were determined as 18.21 (cold press) and 17.33 (Soxhlet) to 31.68 (cold press) and 30.06 mg/g (Soxhlet), respectively. The caper seed oils contained 54.125 (cold press) and 86.63 mg/100 g (Soxhlet) total flavonoid. Total carotenoid and chlorophyll contents of seed oils extracted by cold press were found high. In addition, total phenolic, total flavonoid, and antioxidant activity values of seed oils extracted by Soxhlet were detected as higher. Gallic acid amounts of caper seed oils were determined as 3.70 (cold press) and 5.48 mg/100 ml (Soxhlet). 1, 2‐Dihydroxybenzene amounts of seed oil samples were identified as 5.15 (cold press) and 8.28 mg/100 ml (Soxhlet). The oleic and linoleic acid amounts of oils extracted by the cold press and Soxhlet were detected as 11.67% and 12.08% to 54.25% and 54.22%, respectively. Practical applications: Caper plant grows in many countries of Africa, Asia and South European. It is a source of natural components in the food industry. Cold pressing procedure involves no heat or chemical treatments. Cold press technique is simple and environment‐friendly method. Solvent extraction on the other hand is a cost‐effective and fast method of oil extraction. The current study provides comparison of these two methods to extract natural phytochemicals in caper seed oil.